A novel anaerobic–anoxic/nitrifying-induced crystallization sequence batch reactor (A2N-IC-SBR) process for enhancing phosphorus recovery and nutrient removal. Issue 16 (2nd April 2016) - Shi, Jing; Lu, Xiwu; Xu, Zhengwen; Fang, Mengyuan
Abstract: An anaerobic–anoxic/nitrifying-induced crystallization sequence batch reactor (A2 N-IC-SBR) process was developed for enhanced nutrient removal and phosphorus recovery. The performance of the A2 N-IC-SBR process was investigated in this study. Compared to the A2 N-IC continuous flow (CF) process, A2 N-IC-SBR provided important advantages, including minimal space requirements, ease of enhanced phosphorus recovery, and improved ammonia removal. Percentage of chemical phosphorus removal of total phosphorus removal was 14.9–17.1% in the A2 N-IC-SBR process, while it was 8.0–12.6% in the A2 N-IC-CF. The effluent ammonia concentrations were below 5 mg/L. The A2 N-IC-SBR process met the requirements of Urban Waste Water Treatment Directive 91/271/EEC. Furthermore, ammonia and nitrate concentrations could be simulated satisfactorily in each stage. In addition, an important feature called the self-adjustment characteristic was found, as the system has the ability to cushion the effect of increased or decreased chemical phosphorus removal amount during the process.